Non-linguistic analysis of call center conversations - Kopparapu, Sunil K.; SpringerLink (Online service). (Cham Springer International Publishing, 2015)
The book focuses on the part of the audio conversation not related to language such as speaking rate (in terms of number of syllables per unit time) and emotion centric features. This text examines using non-linguistics features to infer information from phone calls to call centers. The author analyzes "how" the conversation happens and not "what" the conversation is about by audio signal processing and analysis.
Overview -- Voice Analytics Process -- Call Center Linguistic Analytics -- Non-linguistic Speech Processing -- Case Study.-Conclusions.
Electronic reproduction.
Keywords: Speech processing systems; Automatic speech recognition; Computational linguistics; Electronic books